Glaucoma in Childhood - Savleen Kaur; Sushmita Kaushik; Surinder S Pandav (Delhi Journal of Ophthalmology)
Glaucoma in childhood is a potentially blinding condition, yet, there is a lack of epidemiologic and clinical data regarding this pathology. Unlike glaucoma in adults, which is notoriously difficult to detect since there are no symptoms, glaucoma in children does present with signs and symptoms which can be detected by pediatricians and even parents, who are usually the first contacts of these children. Due to the difficulty faced in examining children, glaucoma in the pediatric population is at risk of being misdiagnosed or sub optimally treated, allowing irreversible corneal and optic nerve damage to occur. The childhood glaucoma research network (CGRN) has provided a new classification system of pediatric glaucomas. Careful diagnosis and timely intervention leads to the most promising outcome and gives these children a long morbidity free life.